2022
DOI: 10.51505/ijebmr.2022.6518
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Outward Direct Investment in Africa: From the Perspective of Geopolitics and Cross-cultural Leadership

Abstract: There has been an increase in economic cooperation between China and Africa. The current study investigated the current status of Chinese Outward Direct Investment (ODI) in Africa and the factors that motivate Chinese companies to invest in Africa. Facing the challenges of investing in Africa, the current study suggested that China needed to enhance its soft power by intensifying academic and social exchange between Africa and China. Additionally, leaders working with Chinese companies investing in Africa can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Being two of the most popular fast-food company in China, those two companies have been using very different strategies. The two authors concluded that cultural difference has been a huge influencer on which strategies those two companies chose [1]. Hanaysha looks at brand equity from the customer's view.…”
Section: Related Researchmentioning
confidence: 99%
“…Being two of the most popular fast-food company in China, those two companies have been using very different strategies. The two authors concluded that cultural difference has been a huge influencer on which strategies those two companies chose [1]. Hanaysha looks at brand equity from the customer's view.…”
Section: Related Researchmentioning
confidence: 99%